An unfortunate incident of a surgical swab left in the sphenoid sinus for eight years - Shah, Hamid; Khan, Imran Mohib; Ayub Khan (Journal of the Pakistan Medical Association, 2023)
Retained foreign bodies are foreign materials which are left accidentally inside a patient’s body after a procedure. In this report we present the case of a 57 year old man who presented to the ENT clinic with a history of symptoms stretching over 8 years back to when he underwent a hypophysectomy through the transsphenoidal approach. These symptoms included cacosmia, ageusia, altered taste at times, foul smelling discharge, nasal discharge and dizziness. He had undergone multiple radiological examinations as well as antibiotic courses. It was only after the examination of the nose under general anaesthesia, conducted by the corresponding author that a swab was found in the sphenoid sinus which was left behind from his surgery 8 years ago. Cases of retained foreign bodies are very rare and are easily preventable. This case highlights the importance of adherence to health and safety protocols to prevent such an avoidable complication.